CAN DISTRIBUTED SOFTWARE DEVELOPMENT BE AGILE? - RAMESH, BALASUBRAMANIAM; CAO, LAN; MOHAN, KANNAN; PENG XU (Communications of the ACM, 2006)
The article presents a case study of three U.S.-based companies that develop computer software in cooperation with partners in India. The authors discuss the communications, management, and organizational methods used by the companies in the case study. According to the authors, agile software development methods create communications challenges for work teams that are spread out across continents and oceans. One of the companies adopted a formal communications structure; they appointed an individual at each work site to be the "point person" for project communication. All of the companies found that "real-time" communication was important; as a result, onshore and offshore workgroups adjusted their hours to facilitate communication.